2018
DOI: 10.1016/j.scitotenv.2017.09.319
|View full text |Cite
|
Sign up to set email alerts
|

Effects of agricultural land use on dissolved organic carbon and nitrogen in surface runoff and subsurface drainage

Abstract: Dissolved organic carbon (DOC) load in discharges from cultivated soils may have negative impacts on surface waters. The magnitude of the load may vary according to soil properties or agricultural management practices. This study quantifies the DOC load of cultivated mineral soils and investigates whether the load is affected by agricultural practices. Discharge volumes and concentrations of DOC and dissolved organic nitrogen (DON) were continually measured at three sites from surface runoff and artificial sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 58 publications
3
26
0
1
Order By: Relevance
“…In 2016, a higher volume of manure was added (233 L per plot) than in 2015 because of a lower N concentration. An increase in DOC concentration over the growing season with the use of organic fertilizers (composts) has also been confirmed in a recent study (Manninen et al, 2018). The rather low watersoluble concentration of Mo in our study may be explained by the fact that the strongest adsorption of Mo to the soil occurs at around pH 5 (Smith et al, 1997), which is not different from the pH values measured in the samples from our field experiment in August.…”
Section: Influence Of Biogas Digestates Fertilization On Trace Metalssupporting
confidence: 90%
“…In 2016, a higher volume of manure was added (233 L per plot) than in 2015 because of a lower N concentration. An increase in DOC concentration over the growing season with the use of organic fertilizers (composts) has also been confirmed in a recent study (Manninen et al, 2018). The rather low watersoluble concentration of Mo in our study may be explained by the fact that the strongest adsorption of Mo to the soil occurs at around pH 5 (Smith et al, 1997), which is not different from the pH values measured in the samples from our field experiment in August.…”
Section: Influence Of Biogas Digestates Fertilization On Trace Metalssupporting
confidence: 90%
“…It is estimated that, on a global scale, the amount of DOC that the river networks transport to the oceans is approximately 0.17–0.36 Pg C/year (1 Pg is 10 9 t; Aitkenhead & McDowell, ; Dai et al, ; Harrison et al, ; Li et al, ; Ludwig et al, ). Due to its active biogeochemical properties, DOC can affect the transportation and transformation of other pollutants, such as the complexation of heavy metals, and the effects on the nutrient cycle, which may profoundly impact climate change, damage ecosystems, and increase environmental pollution (Brett et al, ; Manninen et al, ). Hence, riverine DOC has remained an important issue in the context of the global and regional carbon cycle and budget studies for the last few decades.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrate-N was found to be the main type of N loss from agricultural land-use catchments [31]. Generally, the amounts of nitrate-N in runoff water are influenced by N mineralization, local precipitation, crop systems [32] and discharge [13], and soil freeze–thaw cycles during winter could be another dominant factor leading to high N losses and N concentrations in runoff water [33]. In this study, higher losses of nitrate-N were found in the Skuterud catchment than in the Naurstad catchment (figure 4), which may be due to the high temperature, more soil tillage, high N fertilizer application and N surplus in Skuterud, and therefore increased N mineralization [34].…”
Section: Discussionmentioning
confidence: 99%
“…Such a periodic variation is well known in areas dominated by annual crops [22]. Nitrogen loads in agriculture-dominant catchments depend on seasonal conditions [13]. Owing to increased uptake by plants, the lowest N concentrations were observed during the summer months (June–August) [5,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation